Mandated Leave Policies in the Context of Student Mental Health Challenges at Canadian Universities: A Framework Analysis - Green, David S.; Goldstein, Abby L.; Yousaf, Amina; Ansari, Negin (Canadian Journal of Higher Education, 2022)
Although there is increased attention to the mental health needs of university students, far less attention has been given to mental health-related university policies. Many Canadian public universities have mandated leave policies that specify the conditions under which a student may be required to take a leave of absence from university. The purpose of the current study was to conduct an in-depth analysis of current mandated leave policies in public Canadian English-speaking universities. Applied framework analysis methodology was used to examine the approaches to balancing the needs of students experiencing mental health challenges and providing a safe environment on campus. Three primary themes regarding mandated leave policies were identified, including (a) approaches for addressing mental health concerns, (b) balancing the needs of the student with the needs of the institution, and (c) guidelines, standards, and quality assurance. Implications for mandated leave policies and approaches to students experiencing mental health challenges are discussed.